Eksperimentasi Mobile Learning Pada Mata Kuliah Kalkulus Integral Ditinjau Dari Kemampuan Bekerjasama - Siti Suprihatiningsih; Nugroho Arif Sudibyo; Triana Harmini (Universitas PGRI Adi Buana Surabaya, 2020)
The covid-19 pandemic period like now requires to find an alternative learning that is effectively used. It drives a changing method of learning from face-to-face to online. One alternative in learning today is the use of smartphones or commonly referred to as mobile learning. This study aims to determine: 1) differences in student mathematics learning achievement with learning through mobile learning and google classroom, 2) interaction between learning through mobile learning and the ability to work together with students towards mathematics learning achievement, 3) differences in student mathematics learning achievement at the level of ability cooperate. The subjects of this study were students of the Mathematics Education Study Program STKIP Pamane Talino who took 68 Integral Calculus courses consisting of 2 classes. The research was conducted in 5 meetings. Each group was taught with the same material. The instruments in this study were test and questionnaire. The research method used was quasi experiment with 2x3 factorial design approach. The data analysis test used was the two-way ANAVA test with the analysis prerequisites in the form of a normality test and a homogeneity test. The results of data analysis show that the data are normally distributed and homogeneous. Thus, it can be concluded that: (1) learning with Mobile Learning media is more effective than learning with Google Classroom media, (2) the level of ability to work together high, medium and low gives different effects on student mathematics learning achievements and (3) students with all levels of ability to work with learning media Mobile Learning and Google Classroom provide equally good learning achievements.